Masters of Two Arts : Re-creation of European Literatures in Italian Cinema - Testa, Carlo (Book collections on Project MUSE., 2002)
Carlo Testa demonstrates that while pairings of famed directors and writers are commonplace in modern Italian cinema, the study of the interrelation between Italian cinema and European literature has been almost completely neglected in film scholarship.